ANALISIS PENERAPAN PENDEKATAN PEMBELAJARAN MENDALAM PADA PEMBELAJARAN IPA DI SEKOLAH DASAR KELAS III DAN VI - Fatimah Azzahra; Maulida Amalia Zahra; Raushan Fahira Calliesta (CV. ADIBA AISHA AMIRA, 2026)
This study aims to describe and compare the implementation of deep learning principles in science learning at the elementary school level, specifically in Grade III and Grade VI. The problem underlying this research is the tendency of science instruction to emphasize content delivery and memorization, resulting in limited student engagement and shallow conceptual understanding. This study employed a qualitative descriptive approach with a comparative descriptive observational design. Data were collected through classroom observations, brief teacher interviews, and documentation of instructional materials. The research was conducted at SDN Jatinegara 15 Pagi, East Jakarta, involving Grade III science learning on metamorphosis and changes in living organisms and Grade VI science learning on the human movement system. The results show clear differences in the implementation of deep learning across grade levels. In Grade III, deep learning is reflected through concrete and visual activities such as observing images, drawing process stages, and explaining concepts in simple terms. In contrast, Grade VI learning emphasizes analytical and reflective activities, including group discussions, conceptual reasoning, and responding to guiding questions. These findings indicate that the application of deep learning in elementary science learning must be adapted to students’ cognitive development stages to achieve meaningful and sustainable learning outcomes